Chitosan elicited immune response reduces photosynthetic electron transport and ion channel activity in the guard cells of Vicia - Ördög, Attila (Acta Biologica Szegediensis, 2011)
It has been shown that a fungal elicitor chitosan (CHT) inhibits the blue light-induced stomatal opening and can trigger stomatal closure. These movements are related to the H+-ATPase activity in the guard cell (GC) plasma membrane that affects the transport of osmotically active solutes. The ATP for proton pumping is supplied mostly from mitochondrial respiration; however, a partial inhibition by DCMU implies a role of GC photosynthetic electron transport in the ATP supply. In order to investigate whether CHT affects the photosynthetic ATP production of Vicia GCs, the light-dependence of the photosynthetic electron transport rate (ETR) of individual GCs was assayed. In addition, to test the possible effect of CHT on the activity of ion channels, GC protoplasts were investigated by patch clamp technique.